Two topological axes for temporo-spatial processing in dual task visuomotor control - Nissen, Christina; Guldan, Julia; Kajal, Diljit Singh; Gehrig, Johannes; Ding, Hao; Muthuraman, Muthuraman; Pflug, Anja; Kell, Christian Alexander (Cerebral cortex (New York, N.Y. 1991), 2025)
In visuomotor control, the right hemisphere has been associated with visuospatial, and the left hemisphere with visuotemporal processing. In right-handed individuals, asymmetric bimanual tasks result in a preferred use of the left hand for spatial processing and of the right hand for temporal processing. Here, we investigate interhemispheric interactions in the cortical visuomotor network in right-handed participants during asymmetric bimanual isometric movements using magnetoencephalography. The task involved spatially and temporally challenging visuomotor tracking with one hand and a precisely timed ballistic grip with the other creating a dual task scenario with either an optimal or a non-optimal task to hand assignment. When the right hand performed the grip without spatial demands while the left hand performed visuomotor tracking (optimal condition), preparatory broadband partial directed coherence from left premotor to right visuomotor regions were stronger than in the non-optimal condition. In contrast, the non-optimal condition showed stronger preparatory connectivity from right inferior parietal cortex to the left hemispheric visuomotor network. Reduced preparatory interhemispheric connectivity increased the chance of mirror movements during task execution. Our results indicate that the dual task problem is solved by cooperative interactions between specialized cerebral hemispheres with both a left-right and a rostro-caudal axis for temporo-spatial processing.